Regulation and privatisation: The case of electricity - Bernardo Bortolotti; Marcella Fantini; Domenico Siniscalco (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper sheds some light about privatisation in utilities. An empirical analysis based on sales in the electricity sector in 38 countries for the period 1977-97 shows that regulation is a crucial institutional variable in privatisation. Not only does it allow governments to increase the pace of divestiture and to sell higher stakes, but it also maximises proceeds reducing regulatory risk. The revenues-efficiency trade-off loses some relevance in electricity privatisation.
Keywords: G30; L51; 330; Privatisation; Regulation; Privatisierung; Regulierung; Elektrizitätswirtschaft; Welt